Pengaruh Kepemimpinan Terhadap Kinerja Pegawai Pada Kantor Desa Di Kecamatan Tommo Kabupaten Mamuju - Irna Iwah; Andi Irfan; Jumaidah Jumaidah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to determine the influence of leadership on employee performance at the village office in Tommo District, Mamuju Regency. The method used in this study was quantitative with a total of 80 employees who were used as samples with the sampling technique using saturated samples. The data used in this study were primary data obtained directly from data sources using questionnaires. The data analysis method uses simple linear regression analysis, coefficient of determination, validation test, reliability, hypothesis test (T test). The results of testing leadership variables have a positive and significant effect on employee performance variables.